Peran Guru Pendamping Dalam Pelaksanaan Kurikulum Merdeka Di Tk Alam Mahira Kota Bengkulu - Yestika, Triya Dita; Asnawati, Asnawati; Nurwita, Syisva (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the role of assistant teachers in the implementation of the independent curriculum at TK Alam Mahira in Bengkulu City. This study used a qualitative descriptive method. Data were obtained from observations, interviews, and documentation with three data analyses, namely data reduction, data presentation, and conclusions, with information consisting of assistant teachers, classroom teachers, and school principals. The results of this study indicate that the role of assistant teachers in the implementation of the independent curriculum at TK Alam Mahira in Bengkulu City is as follows: 1) as educators, assistant teachers play a significant role in helping students during the learning process, 2) as mentors, they provide guidance to students in overcoming problems and give students freedom to act independently, 3) as trainers, they play an active role in fostering independence in students.